Sustainability as a strategic response to the liability of foreignness: Empowering multilatinas for sustainable development - Ana Maria Gomez-Trujillo; Maria Alejandra Gonzalez-Perez; Juan Velez-Ocampo; Olga Patricia Castaño (Entrepreneurial Business and Economics Review)
Objective: This study explores the role of sustainability as a strategic mechanism for multilatinas to overcome the liability of foreignness (LOF) and drive sustainable development in host countries. It also highlights the intersection of sustainability, business ethics, and internationalisation, focusing on their collective impact on sustainable development and identifying business ethics as a promising area for future research.